2006
DOI: 10.1108/02651330610670442
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated internationalisation: evidence from a late investor country

Abstract: PurposeRecent studies are trying to adapt the explanation of the internationalisation process to new environmental conditions. This paper aims to offer evidence of the existence of a group of firms that use a speeded‐up internationalisation process.Design/methodology/approachCluster analysis and logit regressions are used on a sample of 271 Spanish export firms.FindingsThe results obtained support the claim that substantial differences do exist between fast and gradual internationalising firms. The firms inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 75 publications
0
68
0
5
Order By: Relevance
“…Moreover, Zucchella et al (2007) found that firms belonging to an industrial district, pursuing a niche strategy, and possessing various types of prior experience of international activity internationalize at a high speed. Pla-Barber and Escribá-Esteve (2006) found that a proactive attitude among the management team and marketing differentiation advantages lead to faster internationalization, whereas Luo et al (2005) observed that, among Internet firms, top management experience and firm strengths in innovation and marketing are positively associated with high speed.…”
Section: Temporal Perspective and Speed As A Variablementioning
confidence: 93%
“…Moreover, Zucchella et al (2007) found that firms belonging to an industrial district, pursuing a niche strategy, and possessing various types of prior experience of international activity internationalize at a high speed. Pla-Barber and Escribá-Esteve (2006) found that a proactive attitude among the management team and marketing differentiation advantages lead to faster internationalization, whereas Luo et al (2005) observed that, among Internet firms, top management experience and firm strengths in innovation and marketing are positively associated with high speed.…”
Section: Temporal Perspective and Speed As A Variablementioning
confidence: 93%
“…Spain may be described as a late-investor country (Pla-Barber & Escriba-Esteve, 2006). Before Spain joined the European Economic Community in 1986 it had little FDI abroad, being traditionally a net recipient of FDI.…”
Section: The Sample Of Smesmentioning
confidence: 99%
“…Recent globalization trends have influenced the patterns of internationalization of both large multinational enterprises and SMEs, leading to the emergence of so-called "born globals", that is, firms that from inception are active exporters, with a high percentage of sales from abroad (Oviatt & McDougall, 1994;Pla-Barber & Escriba-Esteve, 2006). 5 In our sample of SMEs the average percentage of sales coming from exports is 19% for the exporters, with 75% of exporters selling abroad less than 30% of their total output, which is not a characteristic of "born-global" companies.…”
Section: The Sample Of Smesmentioning
confidence: 99%
“…Nevertheless, we established a more conservative treshold: firms whose level of exports was more than 25% of their annual sales were regarded as having a consolidated international presence. In this way we eliminated firms with isolated activities abroad, as other studies have previously done (Knight & Kavusgil, 1996, Moen, 2002, Pla-Barber & Escribá-Esteve, 2006, Kuivalainen et al, 2007Milanov & Fernhaber, 2009;Jantunen et al, 2008). requested, together with confirmation of the e-mail address.…”
Section: Influence Of Marketing Capabilities On International Performmentioning
confidence: 99%